PHOTOGRAPHY DEPARTMENT OF PROFESSOR ALEKSANDAR KOSTIĆ – ESTABLISHMENT, ACHIEVEMENTS AND SIGNIFICANCE - Puskas, Nela; Aradjan, Ivana (HEALTH CARE, 2022)
In 1924, Dr. Aleksandar Đ. Kostić, the first Professor of Histology and Embryology and the founder of the Institute of Histology at the Faculty of Medicine in Belgrade, formed the Photography Department within the Institute. The first photographs were microphotographs of histological specimens and a certain number of them were published in 1925 in the Microphotographic Atlas of Normal Histology. However, a greater number of photographs were used for the preparation of microphotograms, that is, black and white diapositives which were shown during lectures and laboratory practices. In the following years, Professor Kostić expanded his photographic topics to pathohistological specimens, urine crystals, and bacteriological samples, operative and autopsy material, and embryological and teratological samples. A particularly important activity of the Department was making photographs of patients. Patients were photographed in hospitals or in the studio of the Photography Department. In addition to photographs, the first films entitled Blood flow in the peritoneal membrane of a frog and Blood flow in the interdigital membrane of a frog were made there. During the Second World War occupation, the Germans took away the photographic equipment and consumables, but after the liberation, at the beginning of 1946, the work was restored. In addition to photography, Professor Kostić organized filming and he directed the first medical films in the first post-war years. The Department was still the center of medical photography at the Faculty, while Professor Kostić was the head until 1952, when he was removed from the Faculty of Medicine due to political reasons.